Hukum Dalam Pendidikan Islam: Sebuah Metode Penyelesaian Sengketa di Luar Pengadilan Sebagai Alternatif Penyelesaian Sengketa Antar Masyarakat Nagori di Kabupaten Simalungun - Abdul Rahman Maulana Siregar; Abdul Razak Nasution (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This research aims to analyze dispute resolution methods outside of court which cannot be separated from the context of Islamic law as an alternative dispute resolution between the Nagori Community in Simalungun Regency. Islamic Law Education has become a method of resolving disputes outside of court and has become a focus in seeking and finding faster and more sustainable solutions to resolve and resolve disputes between communities. It can be concluded that law in the Islamic perspective is not merely in the form of statutory regulations created by the state (state law), but also law in its form as regulations of belief originating from a community belief (customary law/folk law), including It also includes regulatory mechanisms in society (self-regulation) which also function as a means of social control. In addition, law in Islamic education is a method of resolving disputes outside the court which is very important in efforts to reduce the burden on the courts and introduce faster and more sustainable dispute resolution.